What do labor market institutions do? - Holmlund, Bertil (Bonn, 2013)
"The past couple of decades have seen a huge increase in research on various labor market institutions. This paper offers a brief overview and discussion of research on the labor market impacts of minimum wages (MW), unemployment insurance (UI), and employment protection legislation (EPL). It is argued that research on UI is largely a success story, involving a fruitful interplay between search theory and empirical work. This research has established that UI matters for labor market behavior, in particular the duration of unemployment, although there remains substantial uncertainty about the magnitudes of the effects. The research on MW should have shaken economists' belief in the competitive labor market model as a result of frequent failures to find noticeable employment effects despite considerable effects on wages. EPL research has established that employment protection reduces labor and job turnover but the jury is still out regarding the impact on overall employment and productivity."